Relationship between Number of Teats and Litter Size in Eutherian Mammals - Rawal, Deepak (International Journal of Scientific Research in Biological Sciences, 2019)
Mammals are vertebrates with hair and mammary glands, which produce milk for nursing their young. Mammals may be divided into two groups Prototheria and Theria. Prototherian are oviparous and Therian are viviparous. Theria is a subclass of mammals. It includes Eutherians (placental mammals) and metatherians (marsupial mammals). Mammals have a wide variety of skin glands, but all seem to be variations of two major glands, Sudoriferous (sweat) and Sebaceous (oil) glands. Mammary glands appear to be modified sebaceous glands. A teat is the projection from the breast or dug or udder or mammary glands of mammals. A litter is the live birth of multiple offspring at one time in animals from the same mother and usually from one set of parents. In this research we test the hypothesis of Gilbert’s ``one-half rule``. According to one half-rule, the average number of young in a litter is one half the typical numbers of teats and the maximum litter size is equal to the total number of teats. To find relationship between number of teats and litter size, various examples of mammalian species are considered and a comparison and correlation was drawn. In this research we also introduced teat formula (Tf) in mammals for the first time.